Sporting nationalisms : identity, ethnicity, immigration, and assimilation - Cronin, Mike; Mayall, David (Sport in the global society., 1998)
This collection examines the ways in which sport shapes the experiences of various immigrant and minority groups and, in particular, looks at the relationship between sport, ethnic identity and ethnic relations. The essays in this volume are concerned primarily with British, American and Australian sporting traditions and the themes covered include the consolidation of ethnic identity in host societies through participant immigrant sports and exclusive sporting organizations, assimilation into "host" societies through participation in indigenous, national sports, and the construction by outsiders of separate ethnic identities according to sporting criteria.